The Leadership of Kyai In The Special Service Education (A Site Study at PLK Bima Sakti, Nurrusalam Islamic Boarding School, Sayung, Demak) - Ulinuha , Ulinuha (2012)
In the focus, the question to be asked, How are characteristics of the Leadership of Kyai in Special Service Education? The objectives of this study were to describe the leadership of Kyai in academic field at LPK Bima Sakti, Nurussalam Islamic Boarding School, Sayung Demak; and to describe the leadership of Kyai in non academic field at the PLK Bima Sakti, Nurussalam Islamic Boarding School, Sayung Demak. It was a qualitative research using ethnography design. The main subjects of this study were the leader, teacher, and students of PLK Bima Sakti, Nurussalam Islamic Boarding School, Sayung Demak. Interviews, observations, and documentation were the methods to collect data. And for the analysis of data, this study was started by data collection, data reduction, data display, and drawing conclusion. Data validity test used credibility, transferability, confirmability, and dependability. The finding suggested that the leadership of Kyai in academic field at PLK Bima Sakti, Nurussalam Islamic Boarding School, Sayung, Demak was done by the principle of democratic and considering the characteristic of students. Kyai developed the curriculum by the insertion four basic formulas including Siddiq, amanah, tabligh, and fathonah. To support the academic program, Kyai invited outsiders to provide input and guidance such as Department of Social, Department of Education and Sport, and also P2NFI. Leadership of Kyai in non-academic field at PLK Bima Sakti, Nurussalam Islamic Boarding School, Sayung, Demak was done by combining the life skill service programs, social, and religious. The available Life skill services were sewing skill, outbound, workshop, poultry meat, agriculture, fisheries, and automotive. In conducting these activities, Kyai organized entrepreneurial training and skill with the speaker from Sayung, the agricultural Department of Demak, DPD IPSPI Central Java, and college partner. For social service, Kyai prepared students to have a social attitude and be able to interact with the community by asking students to participate in activities of mutual cooperation and community service. To provide religious service, Kyai gave material of Prophet's biography and Sharia with the religion approach, so that students were able to implement it in their everyday life.